Answer:
The last option
Explanation:
• Newton's second law states that the rate of change in momentum is directly proportional to the force applied and it takes the direction of the force.
[tex] \dashrightarrow \: { \tt{ \frac{\delta \: momentum}{time} = force }} \\ \\ \dashrightarrow \: { \tt{f = \frac{mv - mu}{t} }} \\ \\ \dashrightarrow \: { \tt{f = \frac{m(v - u)}{t} }} \\ \\ \dashrightarrow \: { \tt{f = m \{ \frac{(v - u)}{t} \}}}[/tex]
• from first equation of motion:
[tex]{ \bf{a = \frac{v - u}{t} }} \\ [/tex]
substitute:
[tex] \dashrightarrow \: { \tt{f = ma}} \\ \\ \dashrightarrow \: { \boxed{ \tt{ \: \: force = mass \times acceleration \: \: }}}[/tex]
• Assumption taken:
→ mass, m is assumed to be constant
→ the motion is assumed not to start from rest.